Survival advantage of Asian metastatic prostate cancer patients treated with external beam radiotherapy over other races/ethnicities - Würnschimmel, Christoph; Wenzel, Mike; Collà Ruvolo, Claudia; Nocera, Luigi; Tian, Zhe; Saad, Fred; Briganti, Alberto; Shariat, Shahrokh F; Mandel, Philipp; Chun, Felix K H; Tilki, Derya; Graefen, Markus; et al. (World journal of urology, 2021)
PURPOSE: To assess the effect of race/ethnicity in cancer-specific mortality (CSM) adjusted for other-cause mortality (OCM) in metastatic prostate cancer patients (mPCa) treated with external beam radiotherapy (EBRT) to the prostate. METHODS: We relied on the Surveillance, Epidemiology, and End Results (SEER) database to identify Caucasian, African-American, Hispanic/Latino and Asian mPCa patients treated by EBRT between 2004 and 2016. Cumulative incidence plots displayed CSM after adjustment for OCM according to race/ethnicity. Propensity score matching accounted for patient age, prostate-specific antigen, clinical T and N stages, Gleason Grade Groups and M1 substages. OCM adjusted multivariable analyses tested for differences in CSM in African-Americans, Hispanic/Latinos and Asians relative to Cauacasians. RESULTS: After 3:1 propensity score matching and OCM adjustment, Asians exhibited lower CSM at 60 and 120 months (48.2 and 60.0%, respectively) compared to Caucasians (66.7 and 79.4%, respectively, p < 0.001). In OCM adjusted multivariable analyses, Asian race/ethnicity was associated with lower CSM (HR 0.66, CI 0.52-0.83, p < 0.001). Conversely, African-American and Hispanic/Latino race/ethnicity did not affect CSM. OCM rates were comparable between examined races/ethnicities. CONCLUSION: In the setting of mPCa treated with EBRT, Asians exhibit lower CSM than Caucasians, African-Americans and Hispanic/Latinos. This observation may warrant consideration in prognostic stratification schemes for newly diagnosed mPCa patients.
Keywords: senioři; běloši; mortalita; Hispánci a Latinoameričané; Radiotherapy; program SEER; Race/ethnicity; Middle Aged; černoši nebo Afroameričané; mužské pohlaví; nádory prostaty; Hispanic or Latino; Other-cause mortality; míra přežití; nádory kostí; SEER Program; Asian; Carcinoma; radioterapie; Prostatic Neoplasms; Humans; Mortality; Survival Rate; Propensity Score; Black or African American; Američané asijského původu; Bone Neoplasms; Cancer-specific mortality; lidé středního věku; tendenční skóre; Metastatic prostate cancer; White People; Aged; External beam radiotherapy; lidé; Male; karcinom